Formation and Use of Standards for Agriculturally based Products in the New Normal of Global Food Security: Present Challenges and Opportunities for Innovation - Prasetya , Bambang (Current Perspectives in Agriculture and Food Science Vol. 6, 2023)
This chapter describes about the opportunity for innovation and the role of standardization recovery of food security and food safety. The majority of nations in the world, including Indonesia, place a high priority on the agriculture and food sectors. These industries provide a multitude of co-benefits in the areas of the economy, society, and environment. These industries' primary goals are to guarantee food security, create jobs, supply wholesome, high-quality food, and support small- and medium-sized businesses' business integration. The Covid-19 pandemic is a consequence of climate vulnerability with long-standing historical roots in antagonistic anthropogenic activities. To overcome this situation, a number of appropriate activities have been done and some appropriate plans in the middle-long term. In line with that, the opportunities to make an innovation are open based on the lesson learned from the COVID-19 pandemic. Acceleration of formulation standard and its implementation. Key factors affected in the formulation of standards are identified with regard to the recent situation. Sustainable agriculture is achieved through efficient use of farmland. Standards can be valuable tools to bring this to fruition by providing guidance and best practice for machinery, tools and farming methods. National and international Standards for agriculture cover all aspects of farming, from irrigation and global positioning systems (GPS) to agricultural machinery, animal welfare and sustainable farm management. It was also reported that there had been changes to the certification, accreditation, and metrology calibration processes for stakeholder services. Additionally, the role of standards in relation to the World Trade Organization (WTO) and the national system of standardization and conformity assessment were explored. This review's descriptive-analytic methodology is based on literature reviews from a number of scholarly journals, as well as reports issued by associations, international organizations, and governmental bodies.